2019
DOI: 10.1371/journal.pone.0214684
|View full text |Cite
|
Sign up to set email alerts
|

The role of primary intraocular lens implantation in the risk of secondary glaucoma following congenital cataract surgery: A systematic review and meta-analysis

Abstract: This meta-analysis aims to evaluate the incidence of secondary glaucoma in patients under the age of 2 years who underwent congenital cataract surgery with or without primary intraocular lens (IOL) implantation. Methods An electronic literature search was performed in Medline, EMBASE, and Web of Science databases to retrieve studies between January 2011 and November 2018. Patients with congenital cataract who did primary IOL implantation, aphakia, or secondary IOL implantation followed by receiving extraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 34 publications
(36 reference statements)
0
33
0
Order By: Relevance
“…The Spot photoscreener we used in this study has been shown to have good consistency with cycloplegic refraction test in our previous study [ 5 , 31 , 32 ]. It is also reported to have an overall high sensitivity (91.7%) and specificity (82.6%) in detecting amblyogenic risk factors in children [ 10 ], suggesting its good test accuracy.…”
Section: Photoscreening and Corrections For Photoscreener Resultsmentioning
confidence: 90%
“…The Spot photoscreener we used in this study has been shown to have good consistency with cycloplegic refraction test in our previous study [ 5 , 31 , 32 ]. It is also reported to have an overall high sensitivity (91.7%) and specificity (82.6%) in detecting amblyogenic risk factors in children [ 10 ], suggesting its good test accuracy.…”
Section: Photoscreening and Corrections For Photoscreener Resultsmentioning
confidence: 90%
“…Some have used retrospective data to suggest that primary IOL implantation in children is protective against the development of glaucoma. 6,44 However, as identified elsewhere, retrospective data on IOL implantation is unavoidably affected by confounding bias. Intraocular lenses are implanted less commonly in the youngest infants and eyes with significant comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…The thick lens and short axial length of eyeball are very common for the patients with ACG, which could cause shallow anterior chamber and pupillary block to a large extent. [18,19] Nowadays, Phaco is the safe way to deepen the anterior chamber by removing the lens, and the thinner IOL could also eliminate the possibility of pupillary block. Moreover, the intraoperative irrigation pressure in the closed anterior chamber, as well as perfusate flush, also exert forces to reopen the angle.…”
Section: Discussionmentioning
confidence: 99%